2015
DOI: 10.1002/ccd.25858
|View full text |Cite
|
Sign up to set email alerts
|

How bifurcation angle impacts the fate of side branch after main vessel stenting: A retrospective analysis of 1,200 consecutive bifurcation lesions in a single center

Abstract: High BA was an independent predictor of SB occlusion after MV stenting. The occlusion risk of SB with a high BA should not be ignored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…According to our simulations, the bifurcation angle had no significant impact on SB ostium area or SB volume reduction after provisional stent implantation and post-dilation, as the differences between these metrics were minimal between cases with 45º or 70º distal bifurcation angles and the same plaque type. Although this result is in line with clinical studies that have found no correlation between the distal angle and the SB compromise 4,8,29 , other works have identified the presence of a wide 5,12 or narrow 9,13 distal angle as a potential predictor of SB compromise after MB stenting. Significant differences were observed based on plaque composition, with fibrous or lipid plaques having nearly unaffected lumen dimensions, and calcified plaques demonstrating important variations of lumen area and volume, irrespective of the distal bifurcation angle.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…According to our simulations, the bifurcation angle had no significant impact on SB ostium area or SB volume reduction after provisional stent implantation and post-dilation, as the differences between these metrics were minimal between cases with 45º or 70º distal bifurcation angles and the same plaque type. Although this result is in line with clinical studies that have found no correlation between the distal angle and the SB compromise 4,8,29 , other works have identified the presence of a wide 5,12 or narrow 9,13 distal angle as a potential predictor of SB compromise after MB stenting. Significant differences were observed based on plaque composition, with fibrous or lipid plaques having nearly unaffected lumen dimensions, and calcified plaques demonstrating important variations of lumen area and volume, irrespective of the distal bifurcation angle.…”
Section: Discussionsupporting
confidence: 89%
“…Currently, the standard of care to treat a bifurcation lesion is the provisional side branch (PSB) approach 1 . A potential complication of this procedure is the aggravation of side branch (SB) ostial stenosis after stent implantation in the main branch (MB) 1,2 and the associated increased risk of periprocedural myocardial infarction [3][4][5] . SB ostium compromise after PSB has been attributed to plaque shift from the MB into the SB 6 or to the shift of the carina into the SB [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SB branch occlusion during PCI is one of the serious complications in bifurcation treatments and occurs in 7.0%–8.4% of cases . Several mechanisms for SB occlusion have been proposed, including plaque shifting, ostial dissection, spasm, thrombus formation, or ostial coverage by stent strut .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also found that a larger BA before MV stenting was independently associated with a higher SB occlusion rate. We speculated that the increase in BA caused a decrease in the blood flow in the side branch and a reduction in the SB ostial area, which will facilitate SB occlusion .…”
Section: Discussionmentioning
confidence: 99%